PENGARUH PENDIDIKAN KESEHATAN MENGENAI MENARCHE TERHADAP PENURUNAN KECEMASAN SISWI SMP KELAS VII MENJELANG MENARCHE DI SMP NEGERI 1 SEMARAPURA. - Trya Aryaputri Sudjana (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Menarche is first menstruation for a woman when a woman onset in the period of puberty. Based on study of preliminary in the SMP Negeri 1 Semarapura from 10 respondents interviewed said there were 8 respondents very anxious and afraid of the menarche because lack of information or knowledge about menarche. The purpose of this study to know the effect of health education on reducing anxiety about menarche for seventh grade students before menarche at SMP Negeri 1 Semarapura. This study is a pre-experimental one group pre-post test design. Sample of consisted of 87 person chosen by quota sampling. Writer take all of information with giving a questionnaire for students to describe differences of anxiety before giving health education and after giving health education about menarche. The results showed there were 45 respondents (51,7 %) who had mild anxiety before giving health education about menarche and there were 63 respondents (72,4 %) who had mild anxiety after giving health education about menarche. It means health education can be reducing anxiety about menarche seventh grade students before menarche. It is recommended to headmaster to work together with community health centers for giving information about reproductive health for increase the knowledge of the students about reproductive health spesific about menarche .